2021
DOI: 10.1017/s0142716421000503
|View full text |Cite
|
Sign up to set email alerts
|

Why subtitle speed matters: Evidence from word skipping and rereading

Abstract: High subtitle speed undoubtedly impacts the viewer experience. However, little is known about how fast subtitles might impact the reading of individual words. This article presents new findings on the effect of subtitle speed on viewers’ reading behavior using word-based eye-tracking measures with specific attention to word skipping and rereading. In multimodal reading situations such as reading subtitles in video, rereading allows people to correct for oculomotor error or comprehension failure during linguist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Hence, the study by Szarkowska and Gerber-Morón (2018) and Kruger et al (2022) revealed opposing findings that most viewers of their participants could also read the subtitles and follow images. They did so even when the subtitle rates were fast.…”
Section: Discussionmentioning
confidence: 93%
“…Hence, the study by Szarkowska and Gerber-Morón (2018) and Kruger et al (2022) revealed opposing findings that most viewers of their participants could also read the subtitles and follow images. They did so even when the subtitle rates were fast.…”
Section: Discussionmentioning
confidence: 93%
“…This is not the direction that the industry is taking, though. In its most recent SDH guidelines, Netflix (2022) sets a speed of 20 characters per second, which is at the very limit of what hearing viewers can follow (Kruger et al, 2022) and very unlikely to be of use to many viewers with hearing loss. There are, predictably, financial reasons behind this: fast captions are more affordable than slow ones, as they require less editing of the original dialogue and therefore less time to make.…”
Section: The Universal In Media Accessibilitymentioning
confidence: 99%